Deformation behaviour of laser-welded tube blank of TA15 Ti-alloy for gas forming at elevated temperature - Wang Kehuan; Liu Gang; Yuan Shijian (MATEC Web of Conferences, 2015)
Deformation behaviour of laser-welded tube blank of TA15 Ti-alloy at elevated temperature was investigated by both hot tensile tests and high pressure gas forming(HPGF). The hot tensile tests were carried out with four different specimens at 800 ∘C with an initial strain rate of 1.00×10−2 s−1 and HPGF test was performed at 800 ∘C with a constant pressure of 9.5MPa. The tensile results show that base material with equiaxed microstructure exhibited good formability and grain boundary sliding (GBS) accompanied with dynamic recrystallization (DRV) was the main deformation mechanism. However, because the weld bead has coarse columnar grains with fine acicular α′ in the β matrix, when the loading direction is parallel with the weld bead, the fine acicular α′ transformed into thicker α lamella and the aspect ratio decreased greatly, and voids formed along the initial coarse β grain boundaries. When the loading direction is vertical with the weld bead, the welded materials deformed little and the lamella structure thickened obviously after deformation. HPGF tests demonstrate that the laser-welded TA15 tube had a very good formability at 800 ∘C, and the maximum bulging ratio was as high as 77.4%.